2020
DOI: 10.1017/etds.2020.120
|View full text |Cite
|
Sign up to set email alerts
|

Exponential polynomials with Fatou and non-escaping sets of finite Lebesgue measure

Abstract: We give conditions ensuring that the Fatou set and the complement of the fast escaping set of an exponential polynomial f both have finite Lebesgue measure. Essentially, these conditions are designed such that $|f(z)|\ge \exp (|z|^\alpha )$ for some $\alpha>0$ and all z outside a set of finite Lebesgue measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Schubert [10] showed that the Lebesgue measure of the Fatou set of sin(z) is finite in any vertical strip of width 2π. Hemke [7] and the author [13] gave examples of transcendental entire functions whose Fatou set has finite measure. Now the natural question arises whether the Julia set of a transcendental entire function can also have positive measure and still be small in the sense that the Julia set itself has finite measure.…”
Section: Introductionmentioning
confidence: 99%
“…Schubert [10] showed that the Lebesgue measure of the Fatou set of sin(z) is finite in any vertical strip of width 2π. Hemke [7] and the author [13] gave examples of transcendental entire functions whose Fatou set has finite measure. Now the natural question arises whether the Julia set of a transcendental entire function can also have positive measure and still be small in the sense that the Julia set itself has finite measure.…”
Section: Introductionmentioning
confidence: 99%